Grouping of the Second Wave of Covid-19 Infection Areas in East Java Province Using K-Means Clustering - Fadilah Akbar; Edo Leonardo Dekapriyo; Achmad Murtafi Haris; Agoes Moh. Moefad (Jurnal Matematika MANTIK, 2022)
The second wave of Covid-19 Pandemic Attacks that occurred in June 2021 resulted in a drastic number of fatalities. This is due to reduced community responsibility, a sense of caring for each other, and a sense of mutual protection, resulting in the loosening of the health protocols implemented. There needs to be proper mitigation to handle the Covid-19 pandemic properly, one of which is by handling cases in each region with a low level of severity. With this grouping, it can provide a decision on which areas must be available in mitigating the Covid-19 pandemic. For grouping each region, the K-Means Clustering method can be used. From these clusters, there is one area with a severity level, eight areas with moderate severity, and 29 areas with low severity.